2022
DOI: 10.3389/fpls.2022.928176
|View full text |Cite
|
Sign up to set email alerts
|

Differing Responses to Phytophthora cinnamomi Infection in Susceptible and Partially Resistant Persea americana (Mill.) Rootstocks: A Case for the Role of Receptor-Like Kinases and Apoplastic Proteases

Abstract: The hemibiotrophic plant pathogen Phytophthora cinnamomi Rands is the most devastating pathogen of avocado (Persea americana Mill.) and, as such, causes significant annual losses in the industry. Although the molecular basis of P. cinnamomi resistance in avocado and P. cinnamomi virulence determinants have been the subject of recent research, none have yet attempted to compare the transcriptomic responses of both pathogen and host during their interaction. In the current study, the transcriptomes of both avoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 131 publications
4
16
0
Order By: Relevance
“…Downregulation of PaNPR5 was signi cant in both Dusa® and R0.12 at 6 hpi and persisted in Dusa® at 12 and 24 hpi, but not R0.12. Moreover, previous analyses of the data utilized in this study indicated that genes related to growth and developmental pathways were downregulated at 12 and 24 hpi in Dusa®, but not R0.12 [90]. This not only adds support to the putative developmental role of PaNPR5 but to the disparity in the duration of the initial defense responses between Dusa® and R0.12, as growth and defense are generally considered antithetical processes.…”
Section: Activation Of the Npr1-dependent Defense Response Pathwaysupporting
confidence: 65%
See 1 more Smart Citation
“…Downregulation of PaNPR5 was signi cant in both Dusa® and R0.12 at 6 hpi and persisted in Dusa® at 12 and 24 hpi, but not R0.12. Moreover, previous analyses of the data utilized in this study indicated that genes related to growth and developmental pathways were downregulated at 12 and 24 hpi in Dusa®, but not R0.12 [90]. This not only adds support to the putative developmental role of PaNPR5 but to the disparity in the duration of the initial defense responses between Dusa® and R0.12, as growth and defense are generally considered antithetical processes.…”
Section: Activation Of the Npr1-dependent Defense Response Pathwaysupporting
confidence: 65%
“…Whereas 72% and 80% mapped back in the P. cinnamomi inoculated R0.12 and Dusa® samples. A complete report for the data included in this study was recently published [90].…”
Section: Resultsmentioning
confidence: 99%
“…SAR would prime defence responses away from infection sites to prepare cells for future infection. This would explain why the expression levels of PRR genes, which encode receptor-like kinases, increase at 120 hpi in both rootstocks, as reported by Backer et al (2022). A higher abundance of these receptors in uninfected cells would lead to stronger immune response activation once infection does occur (Andam et al, 2020;Palaniyandi & Muthuswamy, 2017).…”
Section: The Expression Patterns For Pamyb and Pawrky Tfs Clearlymentioning
confidence: 73%
“…Furthermore, these expression patterns may explain the differences in callose deposition, PRR and NLR expression patterns previously observed within resistant and susceptible rootstocks following P. cinnamomi infection (Backer et al, 2022;Fick, Swart, Backer, et al, 2022;van den Berg et al, 2018). Because plant-pathogen interactions are extremely complex, the cause of these observations can only be hypothesized.…”
Section: Ap2 Proteins Mainly Regulate Cellular Growth and Differentia...mentioning
confidence: 99%
“…The expression data of 25 PcinCRN effectors were obtained by previously generated dual RNA-seq data of susceptible (R0.12) and partially resistant (Dusa®) P. americana rootstocks inoculated with P. cinnamomi GKB4 [ 50 ]. Briefly, RNA-seq reads were trimmed, and low-quality bases were removed using Trimmomatic v. 0.39 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%